Research of the influence of decomposition of wastes of polymers with nano inclusions on the atmosphere - Vambol, Sergij; Vambol, Viola; Bogdanov, Igor; Suchikova, Yana; Rashkevich, Nina (Eastern-European Journal of Enterprise Technologies, 2017)
We studied the processes of thermo-oxidative decomposition of polymer synthetic waste material with nanoparticles on the example of one of widely spread polymers – synthetic nitron fiber. We carried out a study on the migration of decomposition products and nanoparticles into the environment on a simulation model. We heated the nitronic fibrous material in the temperature range of 150...300 ºС in the presence of oxygen. We stretched the material under investigation until the appearance of fiber breaks. The time of the experiment varied from three to thirty minutes. The REM image of nitron nanofibres obtained by heating the material to 200 °C for 25 minutes demonstrates that fibers are densely packed nanothreads of different length with diameters from 50 to 150 nm. This indicates instability and fragility of the material obtained and the possibility of manifestation of quantum-dimensional effects. We experimentally established gaseous substances, which were released during thermo-oxidative decomposition of polymers, and their concentration, depending on the process temperature on the example of a nitron. Thus, we can consider ammonia and hydrogen cyanide as substances-indicators of latent processes of combustion (smoldering) of materials in a body of a landfill. We need to have a high-precision method of gas analysis to prevent the development of an emergency, since the release of substances occurs already at 100 °C, but in low concentrations. We proposed a remote identification method with a use of a laser complex.